2017
DOI: 10.4269/ajtmh.16-0823
|View full text |Cite
|
Sign up to set email alerts
|

High Triatoma brasiliensis Densities and Trypanosoma cruzi Prevalence in Domestic and Peridomestic Habitats in the State of Rio Grande do Norte, Brazil: The Source for Chagas Disease Outbreaks?

Abstract: A total of 2,431 were collected from 39 populations of Paraíba (PB) and Rio Grande do Norte (RN) states, Brazil. In PB, infection was not detected in either peridomestic or domestic vector populations. In contrast, in RN, was detected with high parasite prevalence in these ecotopes (30.7-40.0%). Moreover, peridomicile insect population densities were more than double the average densities of all other settings evaluated (19.17 versus< 8.94 triatomine/man-hour). Genotyped parasites evidenced a mix of lineages c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
19
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 14 publications
5
19
0
Order By: Relevance
“…There is higher circulation of T. cruzi in Rio Grande do Norte state in comparison to other states which have already been suggested [3]. It was also shown that this high prevalence of natural infection is combined with high populational densities of T. brasiliensis in this state if compared to Paraíba [8]. These findings were confirmed by several authors throughout multiples approaches [23,43,44,45,46,47].…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…There is higher circulation of T. cruzi in Rio Grande do Norte state in comparison to other states which have already been suggested [3]. It was also shown that this high prevalence of natural infection is combined with high populational densities of T. brasiliensis in this state if compared to Paraíba [8]. These findings were confirmed by several authors throughout multiples approaches [23,43,44,45,46,47].…”
Section: Discussionsupporting
confidence: 70%
“…This species remains an operational challenge for vector control because it continually invades and colonizes human domiciles [5,6]. This triatomine was probably involved in recent Chagas disease outbreaks [7] as it was found with high densities and T. cruzi prevalence in domestic and peridomestic habitats around the outbreak area [8]. The difficulty to control T. brasiliensis is attributed to its capacity to occupy the domestic, peridomestic and sylvatic environment [9].…”
Section: Introductionmentioning
confidence: 99%
“…For T. juazeirensis, a member of the T. brasiliensis complex, Carbajal de la Fuente et al [60] found more males than females in light traps, which capture flying insects (dispersants). Lilioso et al [61] captured T. brasiliensis via active search, and they found more than twice males than females in sylvatic environments. This may indicate the existence of distinct patterns of migration between sexes.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, in a recent Chagas disease outbreak in Rio Grande do Norte state, the involvement of T. brasiliensis has been suggested. 29 Home investigation and spraying are highly laborious and costly because native triatomines keep high pressure of domiciliary reinfestation after home spraying with chemical insecticides. Therefore, dwellings can be reinfested few months after treatment.…”
Section: Discussionmentioning
confidence: 99%
“…If on one hand T. infestans could be eliminated because it was restricted to domestic environments in Brazil, then on the other hand native triatomines represent a challenge because they keep foci in the sylvatic environment. Several authors 1,29,30 have stated that not only T. brasiliensis and T. pseudomaculata are able to infest homes in the region. Other local species such as Panstrongylus megistus, Rhodnius nasutus and P. lutzi are also frequently found in domiciles.…”
Section: Discussionmentioning
confidence: 99%